Upaya Peningkatan Motivasi dan Hasil Belajar Mahasiswa dengan Penerapan Model Pembelajaran E–Learning Berbasis Google Classroom pada Masa Pandemi Covid-19 - Daniati Daniati; Bambang Ismanto; Dwi Iga Luhsasi (Jurnal Kependidikan: Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran dan Pembelajaran, 2020)
The purpose of this research is to improve students’ motivation and learning outcomes by applying the Google classroom-based E-Learning model in the Satya Wacana Christian University Economic Education Study Program. The research method used was a classroom action research with the application of 2 cycles. The research subjects were 17 students who took Basic Accounting courses and research objects that took place during the learning process. The data analysis technique used was quantitative descriptive with percentages used to measure the level of student motivation, and for learning outcomes an evaluation was conducted at the end of each lesson. Classroom action research results obtained by implementing Google Classroom could improve students’ motivation and learning outcomes. This improvement could be proved from the implementation of actions starting from pre-action, cycle I, and cycle II. Student learning motivation was said to succeed with an average of 75-100%. The results of the study obtained in the first cycle of action amounted to 74.11% and 80.11% in the second cycle. While the percentage of student learning outcomes had also increased. The increase occurred in pre-action from 50.75 to 73.53 in which the first cycle increased by 22.77, and from 73.53 to 87.35 in the second cycle meaning that an increase amounted to13.82.